One can rewrite the formula for the rotation R in terms of an exponential function. First let us recall that for vectors in the plane the equation for this formula is,

R(θ) = I cos(θ) + G sin(θ).

We can rewrite any vector v in the entire space as the sum of a vector in the plane and another perpendicular to it. So v = Pv + (I - P)v where P is a matrix that projects v onto the ab-plane. If we calculate the square of G = ba

^{T }- ab

^{T}we get

G

^{2}= (ba

^{T}- ab

^{T})(ba

^{T}- ab

^{T}) = b0a

^{T}- b1b

^{T}- a1a

^{T}+ a0b

^{T}= -(aa

^{T}+ bb

^{T})

The part in brackets at the end is a matrix that will project any vector onto the ab-plane so we can let P = -G

^{2}and the rotation formula for any vector will be,

R(θ) = I - P + [I cos(θ) + G sin(θ)]P = I - P + P cos(θ) + G sin(θ)

since GP = G. If we go to the Wikipedia article on matrix exponentials we will find that the expression on the right is just e

^{Gθ}. So we conclude that for simple rotations,

R(θ) = e

^{Gθ}= I - P + P cos(θ) + G sin(θ).

If we note that,

e

^{Gθ}P = P cos(θ) + G sin(θ) then,

R(θ) = I - P +e

^{Gθ}P = I - (I - e

^{Gθ})P,

the formula in the last blog, which works fairly well but isn't as elegant as R(θ) = e

^{Gθ}.

## No comments:

Post a Comment